(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Meeting the growing food needs of the population provides markets for agricultural products. In turn, the relevance of the study is caused by the need to study the composition and diversity of the market, due to the great importance of not only the economic direction, but also the environmental, social. The article considers agricultural markets on the part of their elements, participants, segments and features, illuminates all the variety of types of agri-food market. The factors affecting the change in prices in agricultural markets, as well as the main problems of market development, are disclosed.